Immunomodulatory effect of Echinometra Mathaeis҆ coelomic fluid extract combined with gonad and coelomic extract solely on protoscolices of hydatid cysts in-vitro. (August 2021) - Navvabi, Azita; Homaei, Ahmad; Khademvatan, Shahram; Khadem Ansari, Mohammad Hassan; Keshavarz, Mousa
Abstract: Hydatid disease involves the interaction of Echinococcus granulosus worm with its definitive and intermediate hosts. E. granulosus causes formation of cystic echinococcosis (CE) in humans. In the present study, the scolicidal effect of coelomic fluid extract solely, and in combination with TiO2 and coelomic fluid + gonad extract was evaluated on the liver and lung contaminated with hydatid cysts in-vitro. The immunomodulatory effect of high scolicidal extracts on tumor necrosis factor alpha (TNFα), interferon gamma (IFNγ), and interleukin 5 (IL-5) was assayed. Methanolic coelomic extract was obtained and then, it was incubated with different concentrations of coelomic, coelomic + TiO2, and coelomic + gonad extracts for different exposure times. Coelomic + gonad extract significantly decreased the number of protoscolices. Moreover, scolicidal activity of coelomic extract at 100 μl concentration of the drug was increased over time. The results of our study showed that immunomodulatory effect of coelomic + gonad and coelomic extracts significantly increased expression of TNFα and IFNγ at concentrations of 30 μg/ml and 100 μg/ml, respectively. IL-5 expression was decreased at concentrations of 30 μg/ml and 100 μg/ml. Highlights: The immunomodulatory effect of high scolicidal extracts on TNFα, IFNγ and IL-5 was assayed. Coelomic fluid showed a considerable scolicidal in comparison of albendazole. Coelomic + gonad and coelomic extracts significantly increased expression of TNFα and IFNγ.